2007
DOI: 10.1071/wr05110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a synthetic lure on site visitation and bait uptake by foxes (Vulpes vulpes) and wild dogs (Canis lupus dingo, Canis lupus familiaris)

Abstract: Application of synthetic fermented egg (SFE), via aerosol, to the surface of bait stations increased site visitation by wild dogs and foxes when compared with the use of buried baits alone. An associated increase in bait uptake by foxes at SFE-treated bait stations was observed when compared with bait uptake at untreated stations, although this effect diminished with time, possibly due to the use of non-lethal baits leading to the discovery of all bait stations and the habituation of animals to sites of reward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Additionally, we determined that feral swine preferred -tailed deer 2 43 5 15 53 28 2 30 7 3 26 12 14 56 25 Collared peccary 13 36 36 14 29 48 10 33 30 7 22 32 15 25 60 Rodent 12 26 46 7 15 47 11 11 100 7 12 58 7 19 37 Cattle 2 14 14 7 12 58 6 16 38 6 19 32 9 14 64 Feral swine 5 5 100 5 11 45 6 11 55 6 20 30 4 4 100 Raccoon 7 11 64 3 7 43 0 7 0 7 15 47 4 10 40 Coyote 2 3 67 2 4 vegetable-flavored plus FeralMone baits (100% removal); however, white-tailed deer, collared peccaries, rodents, cattle, raccoons, and opossums also removed this bait type on 14-64% of visits, suggesting that this bait type was not specific to feral swine. Interestingly, coyotes avoided removing bait types with FeralMone attractant added, which was surprising in that FeralMone is based on a proprietary formulation of synthetic fermented egg (Bullard et al 1978) found to increase visitation and bait removal by red foxes (Vulpes vulpes) and wild dogs in Australia (Hunt et al 2007). Also surprising was our observation of visitation and removal of baits with FeralMone attractant by whitetailed deer because synthetic fermented egg has previously been determined to repel deer (Bullard et al 1978).…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Additionally, we determined that feral swine preferred -tailed deer 2 43 5 15 53 28 2 30 7 3 26 12 14 56 25 Collared peccary 13 36 36 14 29 48 10 33 30 7 22 32 15 25 60 Rodent 12 26 46 7 15 47 11 11 100 7 12 58 7 19 37 Cattle 2 14 14 7 12 58 6 16 38 6 19 32 9 14 64 Feral swine 5 5 100 5 11 45 6 11 55 6 20 30 4 4 100 Raccoon 7 11 64 3 7 43 0 7 0 7 15 47 4 10 40 Coyote 2 3 67 2 4 vegetable-flavored plus FeralMone baits (100% removal); however, white-tailed deer, collared peccaries, rodents, cattle, raccoons, and opossums also removed this bait type on 14-64% of visits, suggesting that this bait type was not specific to feral swine. Interestingly, coyotes avoided removing bait types with FeralMone attractant added, which was surprising in that FeralMone is based on a proprietary formulation of synthetic fermented egg (Bullard et al 1978) found to increase visitation and bait removal by red foxes (Vulpes vulpes) and wild dogs in Australia (Hunt et al 2007). Also surprising was our observation of visitation and removal of baits with FeralMone attractant by whitetailed deer because synthetic fermented egg has previously been determined to repel deer (Bullard et al 1978).…”
Section: Discussionmentioning
confidence: 40%
“…We hypothesized that 1) baits with strawberry-flavored feed additive would be specific to feral swine, based on previous findings (Campbell and Long 2008); 2) baits with FeralMonet attractant (Pestat; Proprietary Limited Company, Bruce, Australian Capital Territory, Australia), an aerosolized formulation of synthetic fermented egg, would display high feral swine removal, following findings for carnivores from Australia (Hunt et al 2007); and 3) buried baits would be more specific to feral swine because of the greater below-ground foraging abilities of feral swine compared to nontarget animals.…”
Section: Strawberry-flavored Baits For Pharmaceutical Delivery To Fermentioning
confidence: 99%
“…, 25]. As the attractiveness of lures can also vary with season and location [25, 26], further work is required to determine whether our lack of dhole detection was an artifact of our sampling regime.…”
Section: Discussionmentioning
confidence: 99%
“…Animals which travel to investigate the 'call lure' would move into the range of the 'trap lure' and hopefully interact with the hair trap [e.g., 25]. As the attractiveness of lures can also vary with season and location [25,26], further work is required to determine whether our lack of dhole detection was an artifact of our sampling regime.…”
Section: Discussionmentioning
confidence: 99%
“…Howard et al (1973) Red fox (Vulpes vulpes) 1080: e.g. Thompson and Fleming (1994); Hunt et al (2007); Dundas et al (2014); Kinnear et al (2017) N.D.…”
Section: Rodents (Various Species)mentioning
confidence: 99%